(untitled) (Research Nepal Journal of Development Studies, 2018)
Alternative Rural Development is a conceptual paradigm shift of mainstream economic development of political economy or development economics. It is, to a larger extent, based on Social Welfare Model of Rural Development and Gandhian ideology of Development. The method, strategy and program endogenously designed for Social Justice, Equity and Self Reliance in any underdeveloped country in the third world is Alternative Rural Development. Endogenous sustainable and scientific resource distribution mechanism is Alternative Rural Development. This paper presents the literature review of the Alternative Rural Development paradigm. It gives information and academic inputs about social Justice, Equity, Self–Reliance and Third Worldism. Research Nepal Journal of Development Studies Vol.1(1) 2018 1-17